2022
DOI: 10.1038/s41598-022-08591-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior and performance of ammonium onto sorghum straw biochar from water

Abstract: Sorghum has been widely used for liquor production and brewing, but how to make efficiently utilize sorghum straw (SS) has become an urgent problem. Meanwhile, the wastewater produced by winemaking is typical organic wastewater with a high ammonium concentration. To solve the problem of resource utilization of SS and remove ammonium from water, SS was used to prepare biochar as an adsorbent for ammonium adsorption. Batch adsorption experiments were carried out to study the influencing factors and adsorption me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The SEM images of activated biochars revealed the presence of tunnel‐shaped cracks and cylindrical pores, which acted as diffusion paths for MO molecules (Jjagwe et al, 2021), resulting in the higher sorption of MO compared to raw biochar. The irregular distribution of pores and cracks of activated biochar may favor the sorption of MO by physical trapping and diffusion mechanisms (Wang et al, 2005) reported a similar phenomenon with activated carbon for the sorption of dyes, and oil palm fiber‐derived activated carbon also exhibited such a complex network of pores (Xu et al, 2022) and cracks (Foo & Hameed, 2012). The availability of pores, cracks, and fissures may facilitate the enhanced surface areas of the activated biochar, according to the results obtained from BET surface area results (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…The SEM images of activated biochars revealed the presence of tunnel‐shaped cracks and cylindrical pores, which acted as diffusion paths for MO molecules (Jjagwe et al, 2021), resulting in the higher sorption of MO compared to raw biochar. The irregular distribution of pores and cracks of activated biochar may favor the sorption of MO by physical trapping and diffusion mechanisms (Wang et al, 2005) reported a similar phenomenon with activated carbon for the sorption of dyes, and oil palm fiber‐derived activated carbon also exhibited such a complex network of pores (Xu et al, 2022) and cracks (Foo & Hameed, 2012). The availability of pores, cracks, and fissures may facilitate the enhanced surface areas of the activated biochar, according to the results obtained from BET surface area results (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…In our observed results, for pH 8.5, a higher wavenumber shifts (1,458 → 1,484 cm −1 ) in the biochar adsorbed NH 4 + suggested a surface interaction similar to H‐bonding. In fact, ‐COOH & ‐OH functional groups are ubiquitous in the biochar and are known to engage in surface interactions with NH 4 + (Xu et al., 2022; Yu et al., 2018). Thus, the shift of IR band from 1,458 to 1,484 cm −1 can be rationalized (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Although ammonium adsorption capacity of NaACC was still low when compared with those of other materials such as biochar (7.09 mg/g), 23 mineral clays (40.84–50.06 mg/g), 25 or activated carbon (2.48 mg/g), 18 the biomaterial is derived from an agricultural by‐product, which is abundant and cheap in Viet Nam. Moreover, the production procedure of material is simple and easy to be carried out by non‐expertise people such as citizens in suburban and rural communities.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of NaACC in removal of ammonium as well as its stable-adsorptive capability demonstrated that NaACC derived from agricultural wastes was a potential biomaterial for cleaning ammonium from contaminated groundwater. Although ammonium adsorption capacity of NaACC was still low when compared with those of other materials such as biochar (7.09 mg/g), 23 mineral clays (40.84-50.06 mg/g), 25 or activated carbon (2.48 mg/g), 18 the biomaterial is derived from an agricultural by-product, which is abundant and cheap in Viet Nam. Moreover, the production procedure of material is simple and easy to be carried out by non-expertise people such as citizens in suburban and rural communities.…”
Section: Performance Of Naacc In Ammonium Removal From Natural Ground...mentioning
confidence: 98%
See 1 more Smart Citation